Effect of Okra Fruit (Abelmoschus esculentus) Extract on Granzyme Expression and Tumor Mass Diameter of Adenocarcinoma Mammae: An In Vivo Study - Lugas Lion Halley; Selamat Budijitno; Trilaksana Nugroho; Nani Maharani; Eriawan Agung Nugroho (HM Publisher, 2022)
Background: Breast cancer is currently one of the most common types of cancer suffered by women, with the highest prevalence in all countries in the world. Herbal plants are thought to increase the immune system against tumors, one of which is okra (Abelmoschus esculentus) has the potential as an anti-tumor and anti-carcinogenic. This study aimed to assess the efficacy of ethanol okra extract on granzyme expression and tumor mass diameter in mammary adenocarcinoma of rats treated with adriamycin-cyclophosphamide chemotherapy. Methods: This study is an experimental study using 28 Sprague Dawley Rats. Data analysis was performed with SPSS version 21 to assess differences in granzyme expression and tumor size. Results: The combination of chemotherapy and okra fruit extract (P3) showed optimal potential in increasing granzyme expression and reducing mammary tumor size. Conclusion: The okra fruit extract has potential in the treatment of mammary carcinoma by increasing the expression of granzymes so as to reduce the size of breast carcinoma tumors in vivo.